2012
DOI: 10.3892/ol.2012.688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of a cyclooxygenase-1 selective inhibitor and taxol on proliferation, apoptosis and angiogenesis of ovarian cancer in vivo

Abstract: Abstract. This study was designed to investigate the effects of a cyclooxygenase (COX)-1 inhibitor, SC-560, administered in combination with taxol, on the molecular mechanisms of antitumor efficacy in a SKOV-3 human ovarian carcinoma cell xenograft-bearing mouse model. The mice were treated with 6 mg/kg/day SC-560 by gavage twice every other day and20 mg/kg taxol by intraperitoneal injection once a week for three weeks. Microvessel density (MVD) and vascular endothelial growth factor (VEGF) mRNA levels of ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(49 reference statements)
3
12
0
Order By: Relevance
“…Li found similar results in their in vivo studies (Li et al, 2012a). Li and colleagues also investigated the combination of SC-560 and taxol as well as celecoxib and taxol on the effect of SKOV-3 tumor MVD, apoptosis and VEGF transcript levels (Li et al, 2012a). Taxol in combination with SC-560 was superior to taxol with celecoxib and while the authors did not provide an explanation for the observed differences in the two inhibitors, the potential remains for the possibility of off target or non-COX related effects of the inhibitors (Li et al, 2012a;Li et al, 2013).…”
Section: Cox Enzymes In Ovarian Cancersupporting
confidence: 75%
“…Li found similar results in their in vivo studies (Li et al, 2012a). Li and colleagues also investigated the combination of SC-560 and taxol as well as celecoxib and taxol on the effect of SKOV-3 tumor MVD, apoptosis and VEGF transcript levels (Li et al, 2012a). Taxol in combination with SC-560 was superior to taxol with celecoxib and while the authors did not provide an explanation for the observed differences in the two inhibitors, the potential remains for the possibility of off target or non-COX related effects of the inhibitors (Li et al, 2012a;Li et al, 2013).…”
Section: Cox Enzymes In Ovarian Cancersupporting
confidence: 75%
“…The balance between the proangiogenic and antiangiogenic molecules released by tumor cells and surrounding host cells determines the intense tumor vascularization. Previous studies have demonstrated that VEGF-positive tissue was associated with a high MVD expression, whereas VEGF-negative tissue demonstrated a low expression of MVD, suggesting a positive correlation between VEGF and MVD (28). This result suggests that the potent antiangiogenic activity of brivanib is the primary mechanism of the inhibition of tumor growth in a Hep3B xenograft animal model.…”
Section: Discussionsupporting
confidence: 60%
“…Celecoxib and diclofenac involved VEGF signaling, 45,52) whereas SC-560 did not. 53) Therefore, from the point of view of a decrease in the prevalence of adverse events such as HT and HFSR, SC-560 is recommended in combination with sorafenib for the treatment of HCC. Furthermore, the QOL was considered to be improved in these patients.…”
Section: )mentioning
confidence: 99%